2008
DOI: 10.1016/j.neuron.2008.07.031
|View full text |Cite
|
Sign up to set email alerts
|

The Requirement of Nkx2-1 in the Temporal Specification of Cortical Interneuron Subtypes

Abstract: Previous work has demonstrated that the character of mouse cortical interneuron subtypes can be directly related to their embryonic temporal and spatial origins. The relationship between embryonic origin and the character of mature interneurons is likely reflected by the developmental expression of genes that direct cell fate. However, a thorough understanding of the early genetic events that specify subtype identity has been hampered by the perinatal lethality resulting from the loss of genes implicated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
354
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(376 citation statements)
references
References 59 publications
(87 reference statements)
18
354
1
3
Order By: Relevance
“…Previous studies have shown that loss of Nkx2-1 leads to a respecification of MGE progenitor cells in a temporally regulated manner, which results in the ectopic production of striatal projection neurons and some classes of cortical interneurons (Sussel et al, 1999;Butt et al, 2008). Because these neurons are thought to originate from different rostrocaudal levels of the LGE, these studies demonstrated that the LGE expands at the expense of MGE progenitors in the absence of Nkx2-1 function.…”
Section: Multiple Developmental Origins Underlie Neuronal Diversity Imentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown that loss of Nkx2-1 leads to a respecification of MGE progenitor cells in a temporally regulated manner, which results in the ectopic production of striatal projection neurons and some classes of cortical interneurons (Sussel et al, 1999;Butt et al, 2008). Because these neurons are thought to originate from different rostrocaudal levels of the LGE, these studies demonstrated that the LGE expands at the expense of MGE progenitors in the absence of Nkx2-1 function.…”
Section: Multiple Developmental Origins Underlie Neuronal Diversity Imentioning
confidence: 90%
“…The precise origin of Npas1-expressing GP neurons within the LGE remains to be determined, although previous in utero transplantation experiments suggest that these neurons may originate from the caudal aspect of the LGE, also known as the caudal ganglionic eminence (CGE) (Nery et al, 2002). This region of the subpallium also expresses Pax6 and has been shown previously to be the origin of many tangentially migrating GABAergic neurons (Nery et al, 2002;Butt et al, 2008). Thus, it is possible that Npas1 ϩ neurons in the GP primarily originate from the CGE.…”
Section: Multiple Developmental Origins Underlie Neuronal Diversity Imentioning
confidence: 99%
“…Various transplantation and fatemapping experiments have shown that such a wide diversity is intimately dependent on their birth date and location. Early-born interneurons originate from the MGE and produce mainly the parvalbumin (PV)-and somatostatin (SST)-expressing subtypes, which contribute primarily to deep cortical layers; late-born interneurons derive predominantly from the CGE, generate calretinin (CR)-and vasoactive intestinal peptide (VIP)-expressing interneurons, and preferentially occupy superficial cortical layers (Nery et al, 2002;Xu et al, 2004;Butt et al, 2005Butt et al, , 2008Cobos et al, 2006;Fogarty et al, 2007;Miyoshi et al, 2007Miyoshi et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Диазепам при введении его в высоких дозах вызывает выраженный и стойкий положительный эффект в отно-шении хореи и атаксии пробанда, а быстрое титрование препаратов было возможно без седации других побоч-ных эффектов [40]. В исследованиях на эксперименталь-ных животных было показано, что гаплонедостаточность NKX2-1 нарушает миграцию как дофаминергических, так и ГАМКергических нейронов [7,41], но не установлены физиологические последствия такого состояния. Однако, следует отметить, что в некоторых исследованиях все перечисленные препараты не вызывали какого-либо улучшения в клиническом течении доброкачественной наследственной хореи.…”
Section: патоморфологияunclassified